2018
DOI: 10.3390/app8040485
|View full text |Cite
|
Sign up to set email alerts
|

Raman Imaging for the Detection of Adulterants in Paprika Powder: A Comparison of Data Analysis Methods

Abstract: Raman imaging requires the effective extraction of chemical information from the corresponding datasets, which can be achieved by a range of analytical methods. However, since each of these methods exhibits both strengths and weaknesses, we herein directly compare univariate, bivariate, and multivariate analyses of Raman imaging data by evaluating their performance in the quantitation of two adulterants in paprika powder. Univariate and bivariate models were developed based on the spectral features of the targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Most recently, Raman imaging on both the micro- and macroscale levels have been successfully tested for powdered food authenticity analysis [13,14,15,16,17,18,19]. Since a laser beam can penetrate a certain depth into a sample, the penetration depth was first determined to ensure that the adulterant particles at the very bottom of the sample could be detected [18,20].…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, Raman imaging on both the micro- and macroscale levels have been successfully tested for powdered food authenticity analysis [13,14,15,16,17,18,19]. Since a laser beam can penetrate a certain depth into a sample, the penetration depth was first determined to ensure that the adulterant particles at the very bottom of the sample could be detected [18,20].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that there were significant metabolic differences between high-grade medulloblastoma and normal brain tissue. Lohumi et al [16] used Raman imaging to detect the content of dopants in paprika, by analyzing the univariate, bivariate, and multivariate of the Raman spectra of the substances, the method has effectively reduced the errors caused by the background noise interference. Hauke et al [17] presented a novel approach to in situ studies for the sintering process of silicate ceramics by hyperspectral Raman imaging, which demonstrated the power of hyperspectral Raman imaging for in situ studies of the mechanism(s) of solid-solid or solid-melt reactions at high-temperature with a micrometer-scale resolution.…”
Section: Introductionmentioning
confidence: 99%